Courtesy Isn't Enough For These Non-Smokers - Leto-J; Biorer-I; Grannis-A; Friedman-M; Brand-M (Tufts Archival Research Center, 2007)
New York Post editorials arguing that common courtesy is not enough to protect the rights of non-smokers. Cites medical evidence that second hand smoke is unhealthy. Argues that it is impossible to argue with a smoker.